Private international debt with risk of repudiation - Karsten Jeske (Federal Reserve Bank of Atlanta, 2005)
The risk of repudiation plays a central role in the size and nature of international capital flows. In this paper the author addresses the question of whether, in a world of international capital flows with risk of default, strategic externalities provide a rationale for regulation of international borrowing. The author models centralized arrangements of international debt in which only governments borrow and lend internationally and decentralized arrangements in which individuals have access to international markets. The author shows that a centralized setup allows more international risk sharing than a decentralized setup.
Keywords: 330; Debt; Risk; Capital movements; International finance